Fostering innovation-oriented cultural views among college students through knowledge-building pedagogy. (3rd July 2017) - Hung, Guo-Tsai; Hong, Huang-Yao
ABSTRACT: This study investigated the effects of two different pedagogical approaches on the development of college students' innovation-oriented cultural views. First, an initial cultural view survey (n = 126) was implemented; then another quasi-experiment was employed using two treatment conditions: the control condition (n = 45) employed a concept-centred pedagogical approach, and the experiment condition (n = 31) employed an idea-centred pedagogical approach. The former regards learners as knowledge receivers and highlights learning about important cultural concepts directly from an authoritative knowledge source. In contrast, the latter sees learners as knowledge workers and designers, and emphasises learners' engagement in sustained production and improvement of emergent cultural ideas. Findings based on pre-post essay-writing tests and content-analysis indicate that (1) students tended to relate cultural practices with knowledge transmission activities initially; however, (2) after engaging in idea-centred, design-based pedagogy, students began to see cultural practices as a means to knowledge innovation. Some implications for higher-education regarding innovation-oriented cultural views and awareness were discussed.